New speech tests reveal benefit of wide-dynamic-range, fast-acting compression for consonant discrimination in children with moderate-to-profound hearing loss - Marriage, Josephine E; Moore, Brian C J (International journal of audiology, 2003)
Fast-acting, wide-dynamic-range compression (WDRC) has been shown to give better discrimination of soft speech and shouted speech than linear amplification for moderately hearing-impaired young adults. For severe and profound hearing losses, higher compression ratios are needed. The resultant distortion of the temporal envelope and reduced modulation depth may offset improvements in audibility offered by WDRC. This study compares the effectiveness of WDRC and linear amplification for children with different degrees of hearing loss. Pre-recorded tests of closed-set consonant confusions and open-set word recognition were developed to assess performance. Three groups of subjects (aged 4-14 years) with moderate (51-70 dB), severe (71-90 dB) and profound (91-115 dB) hearing loss were fitted with hearing aids programmed with WDRC or linear amplification. The frequency response was adjusted to match each child's own hearing aid prescription. For each group, stimuli were presented both in quiet and in noise at levels chosen to avoid floor and ceiling effects. Consonant confusion scores for the profound and severe groups combined and for the moderate group were significantly better with WDRC than with linear amplification. Open-set test results showed greater variability. Although mean scores were higher for WDRC than for linear processing, the effects were of marginal statistical significance.